2018
DOI: 10.1111/nbu.12351
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and physical activity countermeasures for sarcopenia: Time to get personal?

Abstract: Population ageing is a global phenomenon. It is regarded as a major cause of upward pressure on healthcare costs. One of the greatest threats to healthy, independent ageing is sarcopenia, the progressive loss of skeletal muscle mass and function with age. Physical inactivity and poor nutrition represent crucial and imminently modifiable risk factors for sarcopenia. Resistance exercise training is the most effective method for improving muscle mass and function in older adults. Evidence indicates that resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 129 publications
0
16
0
Order By: Relevance
“…It is well known that older adults frequently have health-related problems, which may compromise the capacity to perform exercise tasks. Furthermore, since it has been shown that individual responses to nutrition/exercise interventions may be quite variable, a personalized approach to counteract muscle decline seem to be promising [242]. As mentioned above, resistance training is the most effective type of exercise to counteract and/or reverse sarcopenia.…”
Section: Synergies Between Nutritional and Physical Exercise Intermentioning
confidence: 99%
“…It is well known that older adults frequently have health-related problems, which may compromise the capacity to perform exercise tasks. Furthermore, since it has been shown that individual responses to nutrition/exercise interventions may be quite variable, a personalized approach to counteract muscle decline seem to be promising [242]. As mentioned above, resistance training is the most effective type of exercise to counteract and/or reverse sarcopenia.…”
Section: Synergies Between Nutritional and Physical Exercise Intermentioning
confidence: 99%
“…Sarcopenia, or age‐related skeletal muscle loss, is one of the most important causes of loss of independence in older adults, contributing to functional decline, disability, frailty and falls. Physical activity, particularly resistance exercise, and nutrition – particularly protein intake – are both important in slowing this process and reducing its impact (Murphy & Roche ). Muscle mass is estimated to fall by about 8% per decade beyond the age of 40 years, progressing to 15% per decade beyond 70 years of age.…”
Section: Contextmentioning
confidence: 99%
“…Sarcopenia also underpins frailty and the decline in functional capacity that compromises quality of life (6) , and is associated with a range of clinical disorders, such as osteoporosis and obesity (7) . Although the aetiology of sarcopenia is clearly multifactorial and not fully understood (8) , key underlying factors include morphological changes in skeletal muscle (9) , the loss of motor units (10) , physical inactivity (11) and, particularly prudent to this review, dietary protein and energy deficiencies (12) .…”
mentioning
confidence: 99%
“…The combination of adequate dietary protein intake and muscle loading (i.e. resistance) exercise serves as the cornerstone for the management of sarcopenia in both institutionalised and non-institutionalised older adults (1217) . Another key component of an effective countermeasure for sarcopenia includes adequate energy intake (18) , which is typically reduced with ageing (19) .…”
mentioning
confidence: 99%